2020
DOI: 10.1002/uog.22019
|View full text |Cite
|
Sign up to set email alerts
|

Non‐immune fetal hydrops: etiology and outcome according to gestational age at diagnosis

Abstract: Objective Fetal hydrops is associated with increased perinatal morbidity and mortality. The etiology and outcome of fetal hydrops may differ according to the gestational age at diagnosis. The aim of this study was to evaluate the cause, evolution and outcome of non‐immune fetal hydrops (NIFH), according to the gestational age at diagnosis. Methods This was a retrospective cohort study of all singleton pregnancies complicated by NIFH, at the Fetal Medicine Unit at St George's University Hospital, London, UK, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 14 publications
3
35
1
14
Order By: Relevance
“…The rate of ToP in our cohort with 50.8% (183 cases) is consistent with previously published literature (44.3%) [12]. The decision on ToP was associated with etiology, elevated NT thickness, and GA at diagnosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of ToP in our cohort with 50.8% (183 cases) is consistent with previously published literature (44.3%) [12]. The decision on ToP was associated with etiology, elevated NT thickness, and GA at diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…While literature concerning ToP in fetal hydrops is sparse, many investigations have already confirmed high rates of ToP in the case of prenatally detected chromosomal aberration, especially if trisomy 21 was diagnosed [13][14][15]. The association of early diagnosis and ToP is consistent with the results from Sileo et al [12] and relatable due to the expected worse outcome and emotional factors later in pregnancy such as the sense of fetal movement.…”
Section: Discussionsupporting
confidence: 77%
“…This supports the use of ES or whole-genome sequencing (WGS), rather than a targeted or stepwise approach, in the investigation of NIHF 37 . The role of QF-PCR or conventional karyotyping in NIHF should always be respected, given the high incidence of aneuploidy 38 . However, given the limited additional yield of CMA over karyotyping, and considering the ability of WGS to detect both structural variants and aneuploidy, it may be reasonable in the future to consider WGS as the second-line test after QF-PCR 5 .…”
Section: Mone Et Almentioning
confidence: 99%
“…In this study, the median gestational age at the time of diagnosis was 24 weeks (range: 15–36 weeks). In the recent study by Sileo et al, who analysed a group of 279 foetuses with hydrops, the aetiology of NIFH was suggested to vary significantly depending on the gestational age at the time of diagnosis [ 25 ]. This was also observed in our group, as the most common causes of NIHF in the earliest gestational group were aneuploidy and heart defects.…”
Section: Discussionmentioning
confidence: 99%